Character formation 2: leadership, decision making, management and administration. - Garcia, mario A. (Philippines; Wisemans Books Trading, Inc., 2022)
"This book contains Understanding Self-Leadership, Organizational Leadership, Understanding Management, Decision Making, and Understanding Administration. On this face, it tends to orient criminology students on the qualities and effectiveness of leadership by making sound decisions, proper management and administrations that will be involved in".
Includes Bibliographical references.
English Text
Keywords: Decision making Leadership Administrative leadership